KETERLIBATAN ORANG TUA DALAM PENDIDIKAN SPIRITUAL ANAK - Jalal, Novita Maulidya (JCI Publisher, 2025)
This study aims to analyze parental involvement in children's spiritual education as a key factor in their holistic development. Employing a library research method, the researcher explores various literatures on the concepts and practices of parental spiritual education. The findings indicate that active parental involvement, through the application of moral values, behavioral modeling, and open communication, significantly contributes to children's emotional, social, and academic development. The research reveals that children receiving adequate spiritual education are likely to possess better psychological resilience and more mature interpersonal skills. Although challenges such as economic pressures and time constraints hinder spiritual education at home, support from educational institutions and collaboration with the community can enhance its efficacy. The implications of this research highlight the importance of strengthening parental roles in spiritual education to shape children's character and moral identity, as well as to prepare them for future challenges. These findings provide valuable insights for the development of educational policies that emphasize parental involvement in supporting children's spiritual education. Keywords: parental involvement, spiritual education, children.